Integrating AI with Financial Accounting Processes: Innovations and Challenges - Liang, Yaxin; Jiang, Gaozhe; He, Yafeng (International Journal of Computer Science and Information Technology, 2024)
In the context of artificial intelligence (AI), the convergence of advanced technologies has profoundly reshaped financial accounting and management paradigms. This transformation is characterised by the emergence of intelligent finance tools, including integrated industry-financial software and financial robots, which facilitate automated, data-driven processes. These innovations significantly reduce human involvement in routine accounting tasks, leveraging AI capabilities to conduct comprehensive data analysis and enhance decision-making through more profound insights from extensive datasets. Despite these advancements, cybersecurity risks and the necessity for updated theoretical and regulatory frameworks persist. Nevertheless, integrating AI with financial practices holds promise for enhancing operational efficiencies and redefining financial management practices in the digital age.